Dancing with Life: Recontextualizing Mexican Masks: By Pavel Shlossberg, Austin, TX: University of Texas Press/The Northwest Museum of Arts and Culture, 2023. 168 pp. ISBN: 9781477326688. - Cuellar, Manuel R. (Journal of Latin American & Caribbean Anthropology, 2025)
The article focuses on "Dancing with Life: Recontextualizing Mexican Masks," a catalogue accompanying an exhibition at the Northwest Museum of Arts and Culture, which emphasizes the importance of danzas (masked dances) in Indigenous communities of Michoacan, Mexico. The author, Pavel Shlossberg, argues that these performances serve as a means for Indigenous groups to address contemporary sociocultural and political issues, including responses to crises like the COVID-19 pandemic. The catalogue features interviews with local mask makers and performers, highlighting their roles as knowledge producers and guardians of cultural practices, while also addressing challenges posed by neoliberalism and environmental degradation. Shlossberg's work encourages a deeper understanding of the dynamic and adaptive nature of these dances, which are integral to the communities' spiritual and social fabric.